ANALISIS PENURUNAN HASIL BELAJAR MAHASISWA PASCA PANDEMI DALAM PERSPEKTIF KONSTRUKTIVISME - Soraya, Laila; M. Mamduh Winangun (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
The change in the learning system during the COVID-19 pandemic has had a significant impact on the quality of student learning outcomes. The transformation from face-to-face to online learning has led to reduced direct interaction, limited learning experiences, and decreased understanding of the material. This condition has triggered a decline in learning outcomes that is still felt in the post-pandemic period. This article aims to analyze this phenomenon using the perspective of constructivist theory. The method applied is a case study based on secondary data obtained from scientific journals, educational reports, and other relevant sources. The results of the analysis show that the lack of active engagement, minimal contextual experience, and limited interaction during the learning process are the main factors influencing the decline in students' academic abilities. Based on these findings, it is necessary to implement student-centered learning strategies, such as interactive discussions, collaboration, and experience-based learning, in order to improve the quality of learning outcomes.